PRINCIPLES OF MUSIC TEACHERS PROFESSIONAL COMPETENCE FORMATION BY MEANS OF MULTIMEDIA TECHNOLOGIES - Liudmyla H. Havrilova (Інформаційні технології і засоби навчання, 2015)
The article focuses on an urgent problem of contemporary artistic education and concerns implementation of multimedia computer aids of learning in the process of music teachers training. The author considers the principles of music teachers professional competence formation using multimedia technologies and defines them as follows: principle of informatization of learning; principle of visualization, supported with multimedia aids; principle of optimal selection of learning aids; principle of integration of traditional approaches to music education with innovative multimedia technologies; principle of purposeful interaction and creative cooperation between teacher and students; principle of promotion creative musical activities and personal self-expression. Adherence to these principles determines effective professional development of music teachers through the means of multimedia technologies.